2020
DOI: 10.3389/fmed.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Square-Stepping Exercise Program for Older Adults (StepIt): Rationale and Implications for Falls Prevention

Abstract: The ability to effectively execute compensatory steps is critical for preventing accidental falls, and consequently stepping training is an essential ingredient of fall prevention programs. In this paper, we propose a concept for stepping training that aims to maximize training effects by taking into account recent research evidence and a precise dosing of training ingredients. The concept addresses motor as well as cognitive falls-related aspects, it is suitable for individual as well as group based training,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 75 publications
0
20
0
1
Order By: Relevance
“…Recent studies also demonstrated the effectiveness of training programs implemented via new technologies for improving the control mechanisms involved in balance [ 9 , 10 ] and goal-directed locomotion [ 11 , 12 ] in older adults. For instance, specific exergames have been designed to train balance control, focusing on either the static control of the center of mass or its control while performing precise, rapid, and well-directed steps in balance-threatening situations [ 13 , 14 ]. They allow the cognitive and motor demands of the training conditions to be finely controlled during balance control tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also demonstrated the effectiveness of training programs implemented via new technologies for improving the control mechanisms involved in balance [ 9 , 10 ] and goal-directed locomotion [ 11 , 12 ] in older adults. For instance, specific exergames have been designed to train balance control, focusing on either the static control of the center of mass or its control while performing precise, rapid, and well-directed steps in balance-threatening situations [ 13 , 14 ]. They allow the cognitive and motor demands of the training conditions to be finely controlled during balance control tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The execution will be performed at the rhythm given by a metronome. Rhythmic auditory stimulation is a neurological technique that uses the physiological effects of auditory rhythm on the motor system to improve rhythmic movements such as walking [ 47 ]. A pedometer will also be used to verify the volume of physical activity performed [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…In general, taking multidirectional steps in a pattern was shown to enhance motor learning, balance, and memory that could potentially prevent falls (19). It was suggested that SSE is safe and acceptable especially for lower-body functional tness and it may be recommended to older adults due to its low cost and effectiveness (20).…”
Section: Introductionmentioning
confidence: 99%
“…When considering the impacts of health and physical activity in tandem with the needs of the aging population, suitable options for moderate-intensity exercise were needed. A stepping program like the SSE could be modi ed to t different purposes, settings, and populations (19). This study aimed to employ a single case study design to determine if a home-based exercise program for inactive older adults would help overcome barriers and stimulate enablers for regular physical activity following the World Health Organization (WHO) recommendations at the recommended intensity.…”
Section: Introductionmentioning
confidence: 99%